PGal4 excision reveals the pleiotropic effects of Voila, a Drosophila locus that affects development and courtship behaviour. - Grosjean, Y.; Balakireva, M.; Dartevelle, L.; Ferveur, J.F. (Genetics research, 2001)
In Drosophila melanogaster, the PGal4 transposon inserted at the chromosomal site 86E1-2 is associated with the Voila1 allele that causes multiple phenotypes. Homozygous Voila1/1 flies rarely reach adulthood and heterozygous Voila1/+ adult males display strong homosexual courtship behaviour. Both normal behavioural and developmental phenotypes were rescued by remobilizing the PGal4 element. Yet, the rescue of heterosexual courtship and of adult viability did not occur in the same strains, indicating that these defects have different genetic origins. Furthermore, many strains showed a partial rescue of both characters. Molecular analysis revealed that the PGal4 transposon is inserted upstream of the 5'UTR of the prospero gene. The excision strains with no detectable fragment of the PGal4 transposon remaining showed a rescued viability for homozygote adults. Moreover, the developmental period with the highest homozygote lethality was correlated with the size of PGal4 element that remained inserted at the Voila locus. This suggests a relationship between developmental viability and the amount of DNA inserted within the promoter of prospero.